0574 Sleep Duration and Sleep Quality in Association with Risk of Prostate Cancer in the UK Biobank. (25th May 2022) - Freeman, Joshua; Saint-Maurice, Pedro; Watts, Eleanor; Patel, Shreya; Moore, Steven; Matthews, Charles
Abstract: Introduction: Studies of shift work suggest extreme sleep disruption may increase prostate cancer risk. However, studies evaluating sleep duration and quality are inconsistent due to low ascertainment of cases and whether subdomains of sleep quality were queried. Our objective was to evaluate sleep duration, multiple sleep quality domains, and prostate cancer incidence among a large, prospective cohort. Methods: We conducted a secondary analysis among 219399 men aged 40-69 years without prevalent cancer enrolled in the UK Biobank (2006-2010). At baseline participants self-reported their usual sleep duration, difficulties falling or staying asleep, snoring, and falling asleep during the day. We used Cox-proportional hazards models to calculate hazards ratios and 95% confidence intervals for associations with prostate cancer risk. Models were adjusted for confounders. Given potential concerns of reverse causality due to nocturia from undiagnosed prostate cancers increasing sleep disturbances, we restricted the cohort to men with ≥4 years of follow-up in a sensitivity analysis. Results: Over 6.7 years of follow-up, there were 5829 prostate cancer cases. Sleep duration (vs. 7-8 hours; <5 hours HR: 1.08, 95% CI: 0.95, 1.22; 5-6 hours HR: 0.92, 95% CI: 0.85, 1.00; 6-7 hours HR: 0.97, 95% CI: 0.91, 1.03; 8-9 hours HR: 0.93, 95% CI: 0.84, 1.04; ≥9 hours HR: 1.09, 95% CI: 0.91, 1.31) was not associated with prostate cancer. Participants who reported "sometimes" (HR: 1.09, 95% CI: 1.02, 1.16) or "usual" (HR: 1.17, 95% CI: 1.09, 1.26) difficulties falling or staying asleep had greater prostate cancer risk compared to those who reported "never/rarely." Snoring and falling asleep during the day were not associated with prostate cancer. Results were unchanged when restricting to men who had ≥4 years of follow-up. Conclusion: In this large, prospective study, sleep duration, snoring, and falling asleep during the day were not associated with prostate cancer. However, men who had greater difficulties falling or staying asleep had greater prostate cancer risk. These results suggest that poor sleep quality rather than sleep duration may be an important consideration for prostate cancer. Support (If Any): This work was supported by the NIH Intramural Research Program Cancer Research Training Award, NCI.